The Impact of Non-constant Inertia and Nonlinear Damping on the Torsional Vibration Characteristics of Internal Combustion Engine Including External Forces - Lafta, Hameed D. (Kurdistan Journal of Applied Research, 2022)
Failures of the crankshaft-slider mechanism are the most reasons that affect the durability and operational reliability of the internal combustion engine. An accurate and sophisticated nonlinear dynamic model overcomes the obvious simulation errors of linearized models. The present work studies the effect of the non-conservative forces and nonlinear damping on the torsional vibration of single-cylinder internal combustion engines. Comprehensive dynamic modeling based on a developed expression for the instantaneous kinetic energy of the reciprocating parts and a general model of the overall kinetic energy of the system in terms of the inertia parameters were derived. The effect of variable inertia and nonlinear damping on the damped forced response of slider-crank assembly of the engine was investigated using the numerical integration method. The numerical results show that the phenomenon of secondary rolling excitation torque is well activated and gives arises to variation of frequencies and their corresponding amplitudes. Also, the amplitude of the external excitation torque is strengthened by the secondary excitation inertia torque and introduces multi resonance amplitudes phenomenon and widening the critical range of engine speed which results in producing of dangerous vibrational stress amplitudes. Also, the damped forced results indicate that the presents of damping lead to a vital reduction in the amplitude of torsional displacement and excitation torques. The present work aims to enhance nonlinear dynamic modeling and introduces more reliable design for reciprocating engine crankshaft assembly.